2009
DOI: 10.1007/s11605-008-0792-4
|View full text |Cite
|
Sign up to set email alerts
|

Colectomy in Patients with Acute Colitis: A Systematic Review

Abstract: Colectomy for acute colitis is complicated by considerable morbidity. The incidence of adverse outcome has substantially decreased over the last three decades, but further improvements are still required. The retrospective nature of the included studies allows for a considerable degree of selection bias that limits robust and clinically sound conclusions about both conventional and laparoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 63 publications
4
41
1
3
Order By: Relevance
“…We found that complications within 30 days after colectomy occurred in 30 of 77 patients (39%)a frequency of complications comparable to other reports [34,35]. A mortality rate of 2 of 77 patients (2.6%) is also similar to recent reports from the past decade, being in the range 1.5-1.8% [36,37]. The two patients who died after colectomy had substantial comorbidity.…”
Section: Discussionsupporting
confidence: 89%
“…We found that complications within 30 days after colectomy occurred in 30 of 77 patients (39%)a frequency of complications comparable to other reports [34,35]. A mortality rate of 2 of 77 patients (2.6%) is also similar to recent reports from the past decade, being in the range 1.5-1.8% [36,37]. The two patients who died after colectomy had substantial comorbidity.…”
Section: Discussionsupporting
confidence: 89%
“…Urgent surgery is associated with its own morbidity and mortality risks. In a review of recently published articles, the all-cause morbidity and mortality rates associated with surgery for severe colitis were 40.1 and 1.8 , respectively 4 .…”
Section: Discussionmentioning
confidence: 99%
“…76 Pooled results showed high rates of post operative mortality (8%) and morbidity (51%). However, considering only those studies published after 1995, postoperative mortality was only 2% and post operative morbidity was 42%, highlighting the improvements in both medical and surgical management.…”
Section: Short-term Outcomesmentioning
confidence: 97%